Clinical-epidemiological characteristics of early-onset neonatal sepsis in a public hospital, Lima, Peru - Ruiz B., Alessandra (2022)
Objective: To determine the clinical-epidemiological characteristics of newborns with early-onset neonatal sepsis in a public hospital in Lima, Peru, 2016-2017. Materials and methods: An observational, retrospective study of 303 newborns born in Hospital Nacional Dos de Mayo, diagnosed with early-onset neonatal sepsis (2016-2017) and with complete medical records. Maternal variables: age, education, marital status, prenatal care, PROM, type of delivery, UTI, chorioamnionitis, anemia; neonatal variables: sex, gestational age, weight, Apgar, clinical signs, hemoculture, isolated organism, treatment, antibiotic sensitivity. Data processed in Excel and analyzed in SPSS Statistics V25. The incidence of early-onset neonatal sepsis was determined. Results: Incidence of early-onset neonatal sepsis: 67.08/1,000 (2016) and 127.85/1,000 (2017) live births. Incidence of confirmed early-onset neonatal sepsis: 2.98 (2016) and 4.7 (2017). Out of all mothers, 45 % received no adequate prenatal checkup or no checkups; 25 % presented anemia, UTI, history of abortion. Newborns had tachypnea (52.80 %), tachycardia (17.50 %), hypotonia (18.20 %), fever (9.20 %). The therapy included ampicillin-amikacin for probable (86.54 %) and confirmed (85 %) sepsis. Germs, mostly gram positive, were isolated from 8.4 % of the newborns. Coagulase-negative Staphylococcus was the most common bacteria, resistant to clindamycin, oxacillin, ampicillin, cefotaxime, gentamicin, and sensitive to linezolid, vancomycin. Burkholderia gladioli was the only identified gramnegative organism, sensitive to levofloxacin, ciprofloxacin, ceftriaxone but resistant to gentamicin, amikacin. Conclusions: The clinical presentation of neonatal sepsis included tachypnea, tachycardia, hypotonia and fever. Grampositive bacteria were the most commonly isolated species, prevailing coagulase-negative Staphylococci.